LncRNA and mRNA profiles of human milk-derived exosomes and their possible roles in protecting against necrotizing enterocolitis. Issue 24 (30th November 2022) - Yan, Xiangyun; Liu, Linjie; Yao, Shuwen; Chen, Yanjie; Yu, Qinlei; Jiang, Chengyao; Chen, Wenjuan; Chen, Xiaohui; Han, Shuping
Abstract : Human milk derived exosomes show important protective effects against NEC depending on their bioactive components. Further lncRNA and mRNA profiles and their potential roles in protecting against NEC were determined. Abstract : Necrotizing enterocolitis (NEC) is one of the most severe diseases commonly afflicting premature infants. Our previous studies suggests that human milk-derived exosomes (HM-Exos) have a potential therapeutic effect on NEC. In this study, we investigate the potentially therapeutic role of HM-Exos in an NEC animal model via comprehensive lncRNA and mRNA expression profiles. A rat model of NEC was induced through hypoxia, hypothermia and formula feeds. We extracted exosomes from the colostrum of healthy lactating mothers and identified their functions in an NEC animal model. Furthermore, high-throughput lncRNA and mRNA sequencings were explored to find the underlying mechanisms. Although both exosomes from term human breast milk (Term-Exos) and exosomes from preterm human breast milk (Pre-Exos) alleviated the severity of NEC, Pre-Exos seemed to better promote the proliferation of intestinal epithelial cells in vivo . We identified a total of 44 differentially expressed lncRNAs and 88 differentially expressed mRNAs between Term-Exos and Pre-Exos. Further GO and KEGG pathway analysis showed that the lncRNA-mRNA network of HM-Exos was associated with the JAK-STAT signaling pathway, bile secretion and the AMPK signaling pathway, which are predicted to be involved in the proliferation of cells. Therefore, this study reveals for the first time the important roles of human milk derived lncRNAs and mRNAs in protecting against necrotizing enterocolitis. These results provide new insight into the development of NEC.